SYNTHESIS OF ACTIVATED CARBONS ORIGINATED FROM ORANGE PEEL BY SUBCRITICAL CO2 ACTIVATION METHOD - Arenst Andreas Arie; Emerentina Maerilla Puspaningrum; Henky Muljana (Alchemy)
Low-cost and environmental friendly activated carbons were synthesized from orange peel waste by carbonization followed by activation process using supercritical carbon dioxide. The carbonization process of orange peel waste was conducted in the electrical furnace at temperature of 800 °C for 2 h. Activation process of the impregnated orange peel was carried out in the tubular furnace for 1 h at activation temperature of 140 °C and pressure variation of 80, 125 and 170 bar. Activated carbon with highest surface area of 262.173 m2/g was obtained by co2 pressure of 125 bar. The activated carbons were then utilized as adsorbents for removal of methylene blue (MB) from aqueous solution. The batch adsorption study was carried out by varying the initial concentration of mb solution (2, 4, 6, 8 and 10 ppm). Experimental results showed that the adsorption kinetic of mb fitted the pseudo-second-order rate equation, where as for the adsorption isotherm model followed two models i.e. The dubinin- radushkevich and freundlich model. The adsorption mechanism was found to be governed by the intraparticle and surface diffusion mechanism.